2017
DOI: 10.1111/anae.14156
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial comparing high‐flow nasal oxygen with standard management for conscious sedation during bronchoscopy

Abstract: Traditional conscious sedation for endobronchial ultrasound procedures places patients at risk of desaturation, and high-flow nasal oxygen may reduce the risk. We designed a parallel-group randomised controlled trial of high-flow nasal oxygen at a flow rate of 30-70 l.min via nasal cannulae, compared with standard oxygen therapy at 10 l.min via a bite block in adults planned for conscious sedation for endobronchial ultrasound. The primary outcome was the proportion of patients experiencing desaturation (define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
142
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(154 citation statements)
references
References 12 publications
9
142
1
2
Order By: Relevance
“…Successful oxygenation using HFNC during procedural sedation was reported before in adults undergoing bronchoscopy. [10][11][12][13] In their randomized clinical trial Deitch et al 6 demonstrated that adult patients undergoing procedural sedation experienced less hypoxemic episodes if oxygen was applied at 15 L/min compared to room air at the same flowrate.…”
Section: Discussionmentioning
confidence: 99%
“…Successful oxygenation using HFNC during procedural sedation was reported before in adults undergoing bronchoscopy. [10][11][12][13] In their randomized clinical trial Deitch et al 6 demonstrated that adult patients undergoing procedural sedation experienced less hypoxemic episodes if oxygen was applied at 15 L/min compared to room air at the same flowrate.…”
Section: Discussionmentioning
confidence: 99%
“…High‐flow nasal therapy can be delivered to patients who are either breathing or apnoeic. The former group includes patients in acute respiratory failure , during elective and emergency awake airway management and during bronchoscopy under sedation . There is also interest in the use of HFNT in the postoperative setting, for example, following abdominal and cardiac surgery, to reduce the incidence of postoperative pulmonary complications, with mixed results so far .…”
Section: Clinical Usesmentioning
confidence: 99%
“…Its use in anaesthesia is rapidly increasing, providing an alternative to low flow oxygen devices during sedation for procedures such as bronchoscopy and gastroenterology as well as a potential role in non-invasive cardiological, radiological, emergency medicine and persistent pain procedures. [1][2][3] The main advantages of heated and humidified HFNO are improved maintenance of adequate oxygenation with less drying of the upper airway mucosa, thereby improving patient comfort. However, one outstanding question is the role of wave-form capnography during patient sedation when HFNO is administered.…”
Section: Keith B Greenlandmentioning
confidence: 99%